Changes in lipid peroxidation, glutathione, ascorbic acid, vitamin E and antioxidant enzymes in patients with ovarian cancer (Acta Medica Academica, 2008)
Objective. This work was undertaken to assess oxidativestress and antioxidant status in patients with ovarian cancer.Patients and Methods. The study was conducted in thirtyeightpatients with ovarian cancer, the control group being 38healthy volunteers. Erythrocyte lipid peroxidation products(MDA), glutathione (GSH), ascorbic acid, plasma vitamin Eand activities of antioxidant enzymes super oxide dismutase(SOD), glutathione peroxidase (GPX), catalase in erythrocytesand plasma glutathione – S – transferase (GST) were estimatedin ovarian cancer patients. Results. In this study it wasobserved that there was a significant increase in erythrocyteMDA levels, SOD, GPX and plasma GST activities and a significantdecrease in erythrocyte GSH, ascorbic acid, plasmavitamin E levels and catalase activity in patients with ovariancancer when compared to controls. Conclusions. The resultsof our study suggest higher oxygen free radical production,evidenced by increased MDA and decreased GSH, ascorbicacid, vitamin E and Catalase activity, as support to theoxidative stress in ovarian cancer. The increased activities ofantioxidant enzymes may be a compensatory regulation inresponse to increased oxidative stress.
Keywords: Ovarian cancer; Malondialdehyde; Glutathione; Superoxide dismutase; Catalase; Glutathione peroxidase; Glutathione -S - transferase